Re-assessing the relevance and efficacy of yoruba Gods as agents of punishment: a study of Sango and Ogun (2012)
The general objective of this paper was to investigate the relevance and efficiency of Yoruba gods in the administration of punishment and justices on crime commitment. Two Yoruba gods (Sango and Ogun) were principally chosen. Six hundred (600) participants were conveniently sampled from three localities from three geo-political states in the western part of Nigeria. Univariate and bivariate analyses were used in the description of the samples and frequency distribution tables were employed in the presentation of the data. The results show that Yoruba natives still fear and respect these gods. The gods are still relevant and efficient in the administration of punishment on crime commission. The Yoruba natives show preference for the non-conventional punishments of these gods to modern criminal justice systems. Finally, the paper recommends the opinion survey polls on the inclusion of the invocations of these gods in the criminal justice systems of Nigeria and the likely implementations of the invocations in official swearing in ceremony for political and public office holders and the administration of the invocations in Nigerian courts of law.